Conifer plantations in grassland and subtropical forest: Does spider diversity respond different to edge effect?. Issue 5 (3rd September 2018) - Pinto, Carolina M.; Santoandré, Santiago; Zurita, Gustavo; Bellocq, M. Isabel; Filloy, Julieta
ABSTRACT: Two adjacent habitats separated by an abrupt transition often cause strong alterations in environmental conditions resulting in what is called the edge effect. The structural similarity between the adjacent habitats determines how abrupt the transition is. We explored the response of spider communities to the edge effect in mature pine plantations and compared for the first time those responses in contrasting biomes (subtropical forest and grassland) in southern South America. We expect that the higher the contrast between the natural habitat and the conifer plantation, the higher will be the magnitude and the lower the extent of the response of species richness and abundance to edge effect. We sampled spiders using pitfall traps located from the edge to the plantation interior, and environmental variables were measured in pine plantations ( Pinus taeda ) adjacent to native grassland and subtropical forest. Results revealed that wandering spiders were sensitive to edge effect in both subtropical forest and grassland, primarily reflected by a decline in the abundance toward plantation interiors. However, the magnitude and the extent of spider abundance response to the edge effect were similar between pine plantations developing in forest and grasslands biomes. Microclimatic conditions and vegetation cover partially explained species abundance from the edge to plantation interior. Our findings suggest that conifer plantations would promote spider richness if a wide range of microhabitats were provided and support the use of spider abundance to assess edge effect in forested landscapes.